Obtenção e caracterização de novas dispersões sólidas do hansenostático clofazimina - SOUSA, Marcus Lima (2018)
Clofazimine (CFZ) is an antibiotic widely used to treat leprosy. It has high membrane permeability but low aqueous solubility, contributing to a reduction in therapeutic efficacy when administered orally. For active pharmaceutical ingredients that exhibit poor solubility and low bioavailability, the strategic which has proved to be satisfactory is the attainment of novel drug dispersions, such as salts, cocrystals, and co-amorphous. Thus, this work aimed at obtaining and characterizing a new solid dispersion of CFZ, using para-aminobenzoic acid (PABA) as coformer. The new solid dispersions were obtained using the Assisted Liquid Grinding (LAG) method and characterized by X-ray Powder Diffraction (XRPD), Diffuse Reflectance Spectroscopy (DRS), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetry and Differential Thermal Analysis Simultaneous (TG-DTA), and Differential Exploratory Calorimetry (DSC). Application of the LAG in defined molar ratios of CFZ and PABA resulted in a dark purple coloring material, different from the colors of the starting compounds. It observed from the results obtained by XRPD the formation of two new salt-type solid dispersions, one crystalline in the ratio of CFZ-PABA (1:1) and the other amorphous of CFZ-PABA (1:2.68). The structure solved for the salt CFZ-PABA (1:1) showed that the interaction occurred by the formation of the 21(7) synthon. FTIR results suggested that the interaction mechanism form the salt CFZ-PABA (1: 1) and CFZ-PABA (1: 2.68) occurred by protonation of the imino group (isopropyl portion) of CFZ by PABA, and in CFZ PABA 1: 2.68 a second protonation of the imino group (phenazine portion) of the CFZ. The DRS analyzes showed two bands related to the presence of the CFZ-PABA (1:1) and (1:2.68) phases as optimal interaction mole ratios. The results obtained by DTA showed the presence of thermal events related to the glass transition and crystallization in the CFZPABA (1:2.68), confirming the presence of the amorphous phase. Through the DSC analysis, it was possible to construct the binary phase diagram that confirms the formation of the salt CFZ-PABA (1:1). The solubility study demonstrated the increased solubility of CFZ when inserted into the solid dispersions (an increase of 5.0 fold for 1: 1 and of 17.8 fold for 1:2.68). Besides, the applied methodology is more advantageous concerning other crystallization methodologies, since it requires less time of synthesis and less amount of solvent, and the dispersion is also to be possible the getting by melting method. With this, the dispersions require less synthesis time and less or no amount of solvent. Therefore, the solid dispersions synthesized in this work are promising for the production of safer and more effective drugs in leprosy therapy.